Utilização da busca harmônica no ajuste da curva de Weibull em energia eólica - Barbosa, Hélio de Paula (2016)
The wind resource assessment is a key step in the development of wind power generation projects. Minimizing errors in this step brings significant reliability gains for the whole project. In this study we sought a reduction in the errors associated with the adjustment of the Weibull distribution with respect to data collected by an improvement of this setting. With this purpose, it was applied the optimization algorithm of Harmonic Search (HS) to find the Weibull distribution parameters with the best fit. The HS was used to find the Weibull distribution parameters for two sets of data from the Sistema de Organização de Dados Ambientais (SONDA) of the cities of Petrolina-PE and São Martinho da Serra-RS. The parameters of the HS were selected by two methods, one being a result of the novel combination of two other already presented in the literature. We therefore compared the errors for each one to determine which method provides better optimization. For evaluating the quality setting, the root mean square error (RMSE) and the correlation coefficient were used. The HS-PA method uses a selection of random parameters but, results showed more stable than the IHS. It was found for the IHS method one RMSE = 0.006418 for Petrolina and RMSE = 0.008303 for São Martinho da Serra. The HS-PA method presented a RMSE = 0.006419 for Petrolina and RMSE = 0.008303 for São Martinho da Serra. The RMSE values for the traditional methods applied to the same data set, there were two or more times greater than those found by employing the Harmonic search.